Studies in Symbolic Interaction, 33. - Denzin, Norman K. (Emerald Group Publishing, 2009)
The essays in this bi-annual series consist of original research and theory within the general sociological perspective known as symbolic interactionism. Longer than conventional journal-length articles, the essays wed mico and macro concerns within a qualitative, ethnographic, autoethnographic and performance studies orientation. International in scope, the series draws upon the work of urban ethnographers, interpretive, constructionist, ethnomethodological, critical race, postcolonial, feminist, queer, and cultural studies traditions. The emphasis is on new thought and research. Essays which.